Weak economy and strong currency: The origins of the strong yen in the 1990's - Gunther Schnabl (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2001)
During the 1990's the Japanese yen proved astonishingly strong despite the persisting recession. This paper tracks the origins of the high yen. It analyses the influence of interest rates, prices and foreign exchange policy on the yen-dollar exchange rate. It comes to the conclusion that real interest differentials can only explain shortterm exchange rate changes. Since prices have been exe rting their influence on the Japanese currency in the long run, the high yen is explained with deflation. The massive foreign exchange interventions of the 1990's were only able to stop the appreciation temporarily, if they were unsterilized, but they had no lasting effects.
urn:nbn:de:bsz:21-opus-24330
Keywords: 330; Yen; Yen/Dollar Exchange Rate; Foreign Exchange Intervention; Japan; Wechselkurs; Yen; Aufwertung; Zinsdifferenz; Kaufkraftparität; Deflation; Außenhandelspreis; US-Dollar; Japan